UJI AKTIVITAS ANTIBAKTERI Vibrio sp. DENGAN EKSTRAK ETANOL DAUN SIRSAK (Annona muricata L.) - Sianturi, Anggreni; Hitijahubessy, Hendro; Rumangun, Anastasia Putri Marshanda; Samid, Aprianti (Pattimura University, 2023)
Study of the antibacterial ability of soursop leaf extract (Annona muricata L.) in inhibiting the growth of Vibrio sp. The maceration method with 70% ethanol solvent was used in this research to determine the yield, then the extract was diluted in stages from a concentration of 100% to 3.125%. The antibacterial test was done using the disc diffusion method in TCBS media and a phytochemical test was carried out on soursop leaves to analyze the secondary metabolite content. The extract yield obtained in this study was 3.77%. The test results showed that the largest zone of inhibition was found at 100% extract concentration of 11.45mm. The smallest inhibition zone was found in the 6.25% extract with an inhibition zone of 1.44mm, the diameter of the positive control (tetracycline) inhibition zone was 22.75mm, the diameter of 10% DMSO as a negative control was 0 mm. Phytochemical tests of soursop leaves show that they contain alkaloids, flavonoids, steroids, saponins and tannins.